Learning by failing: What we can learn from un-successful entrepreneurship education. Issue 1 (March 2015) - Testa, Stefania; Frascheri, Silvana
Abstract This paper aims to understand why some Entrepreneurship Education (EE) initiatives in secondary schools are ineffective. Specifically, the goal of this paper is to identify mistakes, which could have been responsible for the failures and to derive some useful lessons from them. From a theoretical perspective, it reviews entrepreneurship literature in order to examine the main five constitutive elements of EE in secondary schools: what should the goals of EE be, who should attend EE, who should teach it, what should be taught and how it should be taught. From an empirical perspective, it provides descriptions of the unsuccessful EE initiatives under investigation and discusses failure by collecting the opinions of stakeholders (teachers, principals and students) involved.